Prognostic value of free light chains lambda and kappa in early multiple sclerosis. (October 2017) - Voortman, Margarete M; Stojakovic, Tatjana; Pirpamer, Lukas; Jehna, Margit; Langkammer, Christian; Scharnagl, Hubert; Reindl, Markus; Ropele, Stefan; Seifert-Held, Thomas; Archelos, Juan-Jose; Fuchs, Siegrid; Enzinger, Christian; et al.
Background: Cerebrospinal fluid (CSF) immunoglobulin free light chains (FLC) have been suggested as quantitative alternative to oligoclonal bands (OCB) in the diagnosis of multiple sclerosis (MS). However, little is known on their role in predicting clinical and paraclinical disease progression, particularly in early stages. Objective: To assess the prognostic value of FLC in OCB-positive patients with clinically isolated syndrome (CIS) suggestive of MS and early MS. Methods: We determined FLC kappa (KFLC) and lambda (LFLC) in CSF and serum by nephelometry in 61 patients (CIS ( n  = 48), relapsing-remitting multiple sclerosis ( n  = 13)) and 60 non-inflammatory neurological controls. Median clinical follow-up time in CIS was 4.8 years (interquartile range (IQR), 1.5–6.5 years). Patients underwent 3T magnetic resonance imaging (MRI) at baseline and follow-up (median time interval, 2.2 years; IQR, 1.0–3.7 years) to determine T2 lesion load (T2LL) and percent brain volume change (PBVC). Results: CSF FLC were significantly increased in CIS/MS compared to controls (all p  < 0.001). A lower KFLC/LFLC CSF ratio was associated with CIS-clinically definite multiple sclerosis (CDMS) conversion (hazard ratio (HR) = 2.89; 95% confidence interval (CI) = 1.17–7.14; p  < 0.05). No correlations were found for FLC variables with T2LL or PBVC. Conclusion: Our study confirms increased intrathecal synthesis of FLC in CIS/MS which supports their diagnostic contribution. The KFLC/LFLC CSF ratio appears to have a prognostic value in CIS beyond OCB.